One-Pot Synthesis of 3,4-Disubstituted 2-Methylcyclopent-2-enols as Useful Building Blocks - Jouanneau, Morgan; Tap, Aurélien; Ardisson, Janick; Férézou, Jean-Pierre (Synlett, 2014)
The present study refers to the synthesis of cyclopentene subunits possessing three differentiable functional groups. A triphenylphosphine triggered one-pot Michael–intramolecular Wittig reaction between di-tert-butyl acetylenedicarboxylate and butanedione was made reproducible and scalable, delivering in good yield the desired tricarbonylated building block. Simple and selective transformations of this functionalized cyclopentene were performed.
Keywords: tandem reaction; Michael addition; intramolecular Wittig reaction; cyclization; regioselectivity; diastereoselectivity